T Lymphocyte Immunity in Host Defence against Chlamydia trachomatis and Its Implication for Vaccine Development - X Yang; RC Brunham (Canadian Journal of Infectious Diseases)
Chlamydia trachomatis is an obligate intracellular bacterial pathogen that causes several significant human infectious diseases, including trachoma, urethritis, cervicitis and salpingitis, and is an important cofactor for transmission of human immunodeficiency virus. Until very recently, over three decades of research effort aimed at developing a C trachomatis vaccine had failed, due mainly to the lack of a precise understanding of the mechanisms for protective immunity. Although most studies concerning protective immunity to C trachomatis have focused on humoral immune responses, recent studies have clearly shown that T helper-1 (Th1)-like CD4 T cell-mediated immune responses play the dominant role in protective immunity. These studies suggest a paradigm for chlamydial immunity and pathology based on the concept of heterogeneity (Th1/Th2) in CD4 T cell immune responses. This concept for chlamydial immunity offers a rational template on which to base renewed efforts for development of a chlamydial vaccine that targets the induction of cell-mediated Th1 immune responses.